ANCIENT ART REVISITED ([S.l.])
1 online resource
Keywords: Ancient Art Revisited develops new perspectives on ancient art by weaving together diverse strands within archaeology and art history, exploring it through recent developments in archaeological theory. In order to foster dialogue among various subfields, contributors are drawn from a wide range of domains. Classical archaeology, Aegean prehistory, Near Eastern archaeology, Egyptology, Pre-Columbian South America, and North America are brought together to explore ancient art from multiscalar perspectives and through the lenses of entanglement theory, network thinking, assemblage theory, and other recent theoretical developments. Representing a new wave in research on ancient art, considering both the proximal and distributed operations of artworks, Ancient Art Revisited provides broad and inclusive coverage of ancient art and offers a cohesive approach to a fragmented area of study. This book will be suitable for archaeologists, anthropologists, and art historians wishing to understand the latest thinking on ancient art.